People and Parliament Representative Rights and the English Revolution - Yerby, G. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2008)
This book offers a fresh and rounded perspective on the English Revolution of the 1640s. It uses detailed evidence to show how the economic requirement for parliament's services underpinned a demand for political change. It suggests that this took shape through a working 'discourse' of ideas about the status of representative forms.